Association of ethylene oxide exposure and obstructive sleep apnea - Shanni Ma; Shangfen Xie (Environmental Health and Preventive Medicine)
Background: Ethylene oxide (EO) is a widely utilized industrial compound known to pose health hazards. Although its carcinogenic characteristics have been thoroughly investigated, recent findings indicate possible links to respiratory disease. The correlation between EO exposure and the likelihood of developing obstructive sleep apnea (OSA) in individuals remains unclear. The study aimed to explore the association between EO exposure and OSA within the broader US population. Methods: From 2015 to 2020, 4355 participants were analyzed cross-sectionally in the National Health and Nutrition Examination Survey (NHANES). As the primary indicator of EO exposure, hemoglobin adducts of EO (HbEO) were used in this study. The relationship between EO exposure and OSA prevalence was assessed using weighted multivariable regression analysis and smoothing curve fitting. Using subgroup analysis and interaction tests, we investigated whether this association remained consistent across populations. Results: According to the study, higher HbEO level was positively correlated with a higher prevalence of OSA. Compared to the first HbEO quartile (Q1), participants within the highest quartile (Q4) presented a higher OSA prevalence in the fully model (OR = 1.32, 95% CI: 1.08–1.62, P = 0.01, P for trend = 0.001). This correlation was particularly evident among females and individuals who are insufficiently physically active. Conclusions: This research found a positive relationship between the extent of exposure to EO and OSA prevalence among a representative sample of Americans.